Textbook of animal physiology - Nagabhushanam R; Kodarkar M S; Sarojini R (New Delhi Oxford & IBH Publishing, 1999)
This textbook is organized on the basis of 15 major areas in general & comparative physiology.The 1st chapter gives a survey of electron microscopic structure of an animal cell & cell organelles, physio-chemical properties of protoplasm & plasma membrane
Replacement copy of old acc no 93229
Keywords: Animal physiology